Contemporary digital forensic investigations of cloud and mobile applications - Choo, Kim-Kwang Raymond; Dehghantanha, Ali (Syngress, 2017)
Contemporary Digital Forensic Investigations of Cloud and Mobile Applications comprehensively discusses the implications of cloud (storage) services and mobile applications on digital forensic investigations. The book provides both digital forensic practitioners and researchers with an up-to-date and advanced knowledge of collecting and preserving electronic evidence from different types of cloud services, such as digital remnants of cloud applications accessed through mobile devices. This is the first book that covers the investigation of a wide range of cloud services. Dr. Kim-Kwang Raymond Choo and Dr. Ali Dehghantanha are leading researchers in cloud and mobile security and forensics, having organized research, led research, and been published widely in the field. Users will gain a deep overview of seminal research in the field while also identifying prospective future research topics and open challenges.-Resumé vydavatele
Keywords: forenzní vědy; cloud computing; počítačová kriminalita; mobilní komunikační zařízení; forensic sciences; computer crimes; mobile communication devices; monografie; elektronické knihy; monographs; electronic books